2018
DOI: 10.1210/jc.2018-01227
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Status Predicts Response to Progestin Therapy in Endometriosis

Abstract: Context Progestin-based therapy is the first-line treatment for managing endometriosis-associated pain. However, response to progestins is currently variable and unpredictable. Predictive markers for response to progestin-based therapy would allow for a personalized approach to endometriosis treatment. Objective We hypothesize that progesterone receptor (PR) levels in endometriotic lesions determine response to progestin-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 33 publications
3
69
0
2
Order By: Relevance
“…One potential molecular cause of P4 resistance is a loss or alteration of PGR expression, which has been documented in endometriotic lesions [121,122,123,124,125,126,127,128,129,130] and eutopic endometrium from women with endometriosis [124,130,145,146,147,148]. Further study has confirmed direct correlations between PGR loss with loss of P4-responsiveness in both lesions [149] and cells from the endometrium of women with endometriosis [150]. However, the contribution of PGR loss to the P4 resistance observed in endometriosis is controversial due to a few studies finding no significant difference in PGR levels in eutopic endometrium from women with endometriosis [123,151] or lesions [152].…”
Section: Dysregulation Of Progesterone and Estrogen Signaling In Ementioning
confidence: 87%
“…One potential molecular cause of P4 resistance is a loss or alteration of PGR expression, which has been documented in endometriotic lesions [121,122,123,124,125,126,127,128,129,130] and eutopic endometrium from women with endometriosis [124,130,145,146,147,148]. Further study has confirmed direct correlations between PGR loss with loss of P4-responsiveness in both lesions [149] and cells from the endometrium of women with endometriosis [150]. However, the contribution of PGR loss to the P4 resistance observed in endometriosis is controversial due to a few studies finding no significant difference in PGR levels in eutopic endometrium from women with endometriosis [123,151] or lesions [152].…”
Section: Dysregulation Of Progesterone and Estrogen Signaling In Ementioning
confidence: 87%
“…For example, ER-positive breast cancers, as determined by ER expression in the tumor, are treated with tamoxifen, a selective ER modulator that blocks the effects of estrogen-induced proliferation [ 41 ]. Additionally, PR status is being explored as a potential biomarker of response to progestin-based therapy in endometriosis [ 42 ]. However, the significance of hormone receptor expression for progestin therapy in patients diagnosed with endometrial hyperplasia or adenocarcinoma is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…рецепторы эстрогенов и прогестерона играют определяющую роль в действии стероидных гормонов на клеткимишени. резистентность очагов эндометриоза к действию гормональных препаратов может быть объяснена сниженной или измененной чувствительностью рецепторов стероидных гормонов в эктопических очагах [16][17][18]. считается, что при эндометриозе высокие уровни эстрадиола и эстрогеновых рецепторов стимулируют пролиферацию эндометрия, изменяют нормальный характер генной экспрессии и снижают рецептивность эндометрия [17,19].…”
Section: Discussionunclassified